Harlem renaissance the music & rhythms that started a cultural revolution - Calloway, Cab (Kultur, 2004)
Featuring commentary from historians and the performers themselves, this program traces the roots of the music of the Harlem Renaissance, its social impact on society and its eventual acceptance in mainstream culture